2003
DOI: 10.1074/jbc.m300450200
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Sulfoxide Exposure Facilitates Phospholipid Biosynthesis and Cellular Membrane Proliferation in Yeast Cells

Abstract: Me 2 SO is a polar solvent that is widely used in biochemistry, pharmacology, and industry. Although there are several reports in the literature concerning the biological effects of Me 2 SO, the total cellular response remains unclear. In this paper, DNA microarray technology combined with the hierarchical clustering bioinformatics tool was used to assess the effects of Me 2 SO on yeast cells. We found that yeast exposed to Me 2 SO increased phospholipid biosynthesis through up-regulated gene expression. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 51 publications
7
67
1
Order By: Relevance
“…Additionally, DMSO also leads to decrease in cell number and viability when used at high concentrations [16]. In contrast, it has also been reported that DMSO inhibits the genes involved in lipid biosynthesis but up regulates the genes involved in amino acid biosynthesis in S. cerevisiae [17].…”
Section: Effect Of Dmso On the Physical Parameters Of Bhk Cellsmentioning
confidence: 98%
“…Additionally, DMSO also leads to decrease in cell number and viability when used at high concentrations [16]. In contrast, it has also been reported that DMSO inhibits the genes involved in lipid biosynthesis but up regulates the genes involved in amino acid biosynthesis in S. cerevisiae [17].…”
Section: Effect Of Dmso On the Physical Parameters Of Bhk Cellsmentioning
confidence: 98%
“…We tested this hypothesis as follows. We used the expression data compiled by Dr. Andre Boorsma and Prof. Harmen J. Bussemaker to compute, for each neighboring pair of genes, the Pearson's correlation coefficient of their expression in about 900 experiments (see references [20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38] for the original publications). These coefficients were usually low (< 0.3).…”
Section: Statistical Testsmentioning
confidence: 99%
“…and Aspergillus spp. that correlates well with standard methods.Recent advances in fluorescent-probe technology may permit the use of these reagents in assessing the alteration of physiologic function due to antifungal agents (1,5,6,11,12,23). Therefore, we investigated the utility of a fluorometric assay using the fluorescent probes carboxyfluorescein diacetate (CFDA) and dihexyloxacarbocyanine iodide (DiOC 6 ) to assess the in vitro antifungal activities of amphotericin B deoxycholate representing the class of membrane-active polyenes and caspofungin representing the class of cell wall-active echinocandins (7).…”
mentioning
confidence: 99%